Prevention of Tax Criminal Offences as a Factor in the Financial Stability of the State - TOPCHII, Vasyl; MOROZ, Yuliia; KARPENKO, Natalia; KHORONOVSKYI, Oleg; TARASHCHENKO, Volodymyr (Theoretical and Practical Research in Economic Fields, 2025)
Effective counteraction to tax offences strengthens the financial stability of the state and ensures the filling of the state budget. The aim of the research is to compare the effectiveness of measures to prevent tax offences, applied separately and in combination, using the example of developed economies and developing countries. The research employed correlation, regression analyses, and mediation testing. The study found that the introduction of innovative technologies in the tax sphere can increase the efficiency of detecting tax offences and reduce tax evasion. The effectiveness of the use of Artificial Intelligence (AI), electronic invoice mechanisms, Robotic process automation (RPA), Application programming interfaces (API), Cloud computing was confirmed. The impact of AI and electronic invoice mechanisms is mediated by the efficiency of tax audits, where these technologies can be useful for automation, increasing accuracy and scalability. It is proven that the effective implementation of technologies also depends on the amount of expenses incurred, as well as investment in infrastructure and human resources (HR). The findings may be useful for government officials in the development of tax policy and determining the most effective measures to combat tax evasion.